Early Childhood Language Development of Gadget Users Viewed from Behavioristic Theory - Kusmanto, Desi Ariani; Prihatin, Titi; Sugiyo Pranoto, Yuli Kurniawati (Journal of Primary Education, 2021)
Nowadays, gadgets can be utilized as a tool to stimulate children’ language growth and development. The research is intended to determine the response of early childhood due to the use of gadgets screen as a stimulus for children's language development viewed from behavioristic theory. There are 3 subjects in this research, namely early childhood aged 30-50 months. This research method employs a naturalistic approach. The result reveals that gadgets as a stimulus for early childhood language development viewed from behavioristic theory show different responses, namely 2 children give a negative response and 1 child with a positive response. The negative response is the child experiences speech delays, while the positive response is the child master’s foreign vocabulary and is more expressive in retelling what the child watches from the gadget. Furthermore, it can be concluded that gadget as a stimulus for language development generates negative and positive responses for early childhood, so that adults should be judicious in facing the children by paying attention in some cases, such as timing in using gadgets, content, types of assistance, and giving them many proportions to interact directly.